Management turnover of a Pump Irrigation System in the Philippines: the farmers' way - Gonzáles, L.S. (International Irrigation Management Institute, 1993)
Case study about the implementation of the Farmer Irrigators' Organizing Project in a pump irrigation system in The Philippines employing several selected and well-trained farmers in organizing co-farmers.